Reward and Punishment dalam Perspektif Pendidikan Islam - Wahyudi Setiawan (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2018)
Realizing the nature of the purpose of education is our duty together. A variety of efforts in achieving the goal of education is carried out by all parties, ranging from models, devices, education/educators, and parents together. Reward and punishment is part of the model and strategy in education. A cornerstone in the application of reward and punishment found in the human psychic instincts will feel pleasure when accepting gifts and grieve while receiving punishment. In Islam, there are several verses of the Quran which explains about reward and punishment, and in the West, there is a psychological theory that explains the importance of reward and punishment. Reward aims to provide motivation and a new spirit for the children so that repetition of the conduct plus behaviour, while the punishment is given to give a deterrent effect to the child and deliver a message to other children so as not to do the violation of a rule.